Effect of heat stress on serum testosterone level in rabbits - BAHGA, C S; HANDA, M C (The Indian Journal of Animal Reproduction, 2023)
Nine Soviet Chinchilla and nine Angora male rabbits aged 16-28 months and weighing 2.73 - 3.68 kg. were divided into three groups of six each. Group I was kept in a pen measuring 5.40x2.80x2.90 m and cooled by a ceiling fan (48"). Group II was kept in the pen having the same dimensions as in Group I but cooled by a ceiling fan and a desert cooler. Group III was kept in a shed having dimensions 25.20xl2.80x2".90 m and fitted with 12 fans at a distance of3.20m from each other. The average ambient temperature in Group I, II and Ill was 31.6 I± 0, 14; 28.88 ± 0.13 and 31.30 ± 0. I 7°C, while the corresponding values of relative humidity were 65.98 ± 0.86 ; 78.65 ± 0.83 and 68.03 ± 0.89 per cent . Treatment II provided the most comfortable climatic conditions followed by Treatment III and I. The values of serum testosterone were highest in treatment II (2.62 ± 0.41 ng / ml) followed by treatment III (1.92 ± 0.02 ·ng/ml) and treatment I (1.25 ± 0.35 ng/ml). It can be concluded that heat stress depresses serum testosterone levels and it may be one of the main factors leading to lower reproductive efficiency in males in summer.